1969
DOI: 10.1210/jcem-29-1-92
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of HCG in Man

Abstract: The metabolic clearance rate (MCR) of human chorionic gonadotropin (HCG) was determined in normal male and female subjects following the intravenous and intramuscular administration of 10,000 IU of HCG. The mean MCR (I/day) in the iv experiments was 3.38 for men and 3.86 for women. These values are approximately 1/10 of the MCR value reported for human luteinizing hormone. Following the iv administration, the plasma disappearance curve showed an initial fast component with a half-life of 5.1 and 5.6 hr for mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1
3

Year Published

1979
1979
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(38 citation statements)
references
References 18 publications
3
31
1
3
Order By: Relevance
“…This pattern of response was typical ofthat seen in man (14) and is in marked contrast to the pattern seen in the laboratory rat, perhaps because of the prolonged halflife ofhCG in man when compared with the rat (15,16). Stimulation of the rat testis in vivo leads to a testosterone response within 15 min and a 5-to 10-fold increase by [2][3][4][5][6][7][8][9][10][11][12] h, followed by a decline to normal levels within 1-2 d depending upon the administered dose of gonadotropin (1,2).…”
Section: Resultsmentioning
confidence: 53%
“…This pattern of response was typical ofthat seen in man (14) and is in marked contrast to the pattern seen in the laboratory rat, perhaps because of the prolonged halflife ofhCG in man when compared with the rat (15,16). Stimulation of the rat testis in vivo leads to a testosterone response within 15 min and a 5-to 10-fold increase by [2][3][4][5][6][7][8][9][10][11][12] h, followed by a decline to normal levels within 1-2 d depending upon the administered dose of gonadotropin (1,2).…”
Section: Resultsmentioning
confidence: 53%
“…We gave purified hCG by continuous infusion, and our value for the MCR of hCG is 3.31+0.23 ml/min (or 1.88+0.08 ml/min per m2). In contrast, previous studies ofhCG metabolism employed analysis ofits disappearance after a single injection of crude preparations ofhCG (2,3,5), or after removal ofhCG-producing tissue, e.g., delivery of the placenta (1,4). For example, Wide et al (2) calculated an MCR based on bioassay measurement of hCG of 2.33 ml/min; when a radioimmunoassay was used to measure hCG, these authors found a substantially different value of the MCR, [6][7][8][9][10] h; however, the latest time point at which the hCG level was determined was 24 h in two subjects and 5 h in the third.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolism of human chorionic gonadotropin (hCG)1 has been the subject of a number of reports during the past 40 yr (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). It has been established that the hCG molecule has a plasma metabolic clearance rate (MCR) that is quite slow relative to the MCR of the pituitary glycoprotein hormones (1)(2)(3)(4)(5), and that urinary excretion accounts for some, but not all, of the metabolic disposal of hCG (1,2,(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations